Pengaruh Budaya Organisasi terhadap Kinerja di CV. Sinar Mojokerto - Totok Yulaidin (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of organizational culture on employee performance at CV. Sinar Mojokerto. Organizational culture plays a vital role in shaping employee behavior and performance, especially through elements such as discipline, teamwork, work ethic, and a sense of responsibility. A strong and consistent culture is believed to foster a positive work environment that supports employee productivity. This research uses a quantitative approach with a survey method, involving 50 employees as respondents. Data were collected using a structured questionnaire and analyzed through simple linear regression to determine the strength and direction of the relationship between organizational culture and employee performance. The findings reveal that organizational culture has a positive and significant impact on employee performance. In particular, employees who perceive a strong culture of discipline and cooperation tend to demonstrate higher levels of effectiveness and responsibility in their work. The results suggest that by consistently implementing and strengthening organizational values, companies can enhance employee motivation, improve work outcomes, and achieve overall organizational goals more efficiently. Therefore, organizational culture should be seen not only as a supporting element but as a strategic factor in performance management and organizational development.